Inter-pregnancy interval and risk of recurrent pre-eclampsia: systematic review and meta-analysis - Cormick, Gabriela (Reprod Health, 2016)
BACKGROUND: Women with a history of pre-eclampsia have a higher risk of developing pre-eclampsia in subsequent pregnancies. However, the role of the inter-pregnancy interval on this association is unclear. OBJECTIVE: To explore the effect of inter-pregnancy interval on the risk of recurrent pre-eclampsia or eclampia. SEARCH STRATEGY: MEDLINE, EMBASE and LILACS were searched (inception to July 2015). SELECTION CRITERIA: Cohort studies assessing the risk of recurrent pre-eclampsia in the immediate subsequent pregnancy according to different birth intervals. DATA COLLECTION AND ANALYSIS: Two reviewers independently performed screening, data extraction, methodological and quality assessment. Meta-analysis of adjusted odds ratios (aOR) with 95 % confidence intervals (CI) was used to measure the association between various interval lengths and recurrent pre-eclampsia or eclampsia. MAIN RESULTS: We identified 1769 articles and finally included four studies with a total of 77,561 women. The meta-analysis of two studies showed that compared to inter-pregnancy intervals of 2–4 years, the aOR for recurrent pre-eclampsia was 1.01 [95 % CI 0.95 to 1.07, I(2) 0 %] with intervals of less than 2 years and 1.10 [95 % CI 1.02 to 1.19, I(2) 0 %] with intervals longer than 4 years. CONCLUSION: Compared to inter-pregnancy intervals of 2 to 4 years, shorter intervals are not associated with an increased risk of recurrent pre-eclampsia but longer intervals appear to increase the risk. The results of this review should be interpreted with caution as included studies are observational and thus subject to possible confounding factors. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12978-016-0197-x) contains supplementary material, which is available to authorized users.